Analysis of the Relationship of Domestic Sea Transportation to the Gross Regional Domestic Product of the Real Estate Sector in Indonesia - Nur Alfionita, Firda Bunga; Setiawan, M Ikhsan; Prawito, Adi; Koespiadi, Koespiadi; Durrotun N, Ronny; Ismawati, Ismawati; Sutapa, I Ketut (Malikussaleh University, Aceh, Indonesia, 2024)
The economic slowdown due to the pandemic has negatively affected various sectors in Indonesia, including the real estate sector. Meanwhile, Java Island is still the center of the economy in Indonesia. This contrasts the conditions of regions outside Java, which are still experiencing development gaps. Despite being a minor contributor to GDP, areas outside Java, such as Maluku and Papua, have experienced rapid economic growth. This proves that, outside Java, there is still significant potential for growth and investment, although it is inevitable that it will face unique challenges and obstacles in the future. Some of the factors that cause this to happen are the lack of supporting infrastructure such as roads, limited skilled human resources, and connectivity and transportation mobilization in the area. Excellent and appropriate connectivity and mobilization are needed to support economic growth in an area. One option for mobilization tools for archipelagic countries like Indonesia is sea transportation. In meeting the needs of the property and real estate sector, sea transportation is one of the options of choice. Excellent and proper connectivity and mobilization can be a factor that supports economic growth as well as the real estate sector outside Java. In the real estate sector, maritime transportation is essential in the timely distribution of quality building materials and construction equipment to development sites. There is undoubtedly a link between marine transportation and property/real estate in Indonesia. The research method used in this study is a significant correlation analysis, namely Pearson Product Moment, to determine the relationship between two variables, namely Domestic Sea Transportation and Real Estate Sector GRDP. The results of the correlation data test in this study show that the Domestic Sea Transportation variable is positively correlated with the Real Estate GRDP variable. Indicated by the correlation coefficient value for each sea transportation variable of domestic ship visits (units) = 0.331, domestic ship visits (GT) = 0.504, the flow of Non-Crate and Container goods (unloading) = 0.251, the flow of Non-Crate and Container goods (loading) = 0.447. It can be interpreted that there is a positive relationship between the four sea transportation variables and Real Estate GRDP.